One-pot synthesis of ultrasmall MoO3 nanoparticles supported on SiO2, TiO2, and ZrO2 nanospheres: an efficient epoxidation catalyst - Chandra, Prakash; Doke, Dhananjay S.; Shubhangi B. Umbarkar; Biradar, Ankush V. (Journal of Materials Chemistry A, 2014)
Ultrasmall molybdenum oxide (MoO3) nanoparticles supported on various (SiO2, TiO2 or ZrO2) nanospheres were synthesized in one pot using a reverse micelle method. The prepared catalysts were thoroughly characterized by various physico-chemical methods. TEM images showed uniform dispersion of MoO3 nanoparticles (1.5-4 nm) onto silica (similar to 275 nm). No separate MoO3 particles were identified from TEM for MoO3/TiO2 (similar to 10.5 nm) and MoO3/ZrO2 (similar to 6.5 nm) because AHM reacted with titanium and zirconium hydroxides to form solid solution. Among the prepared catalysts MoO3/SiO2 showed excellent catalytic activity (up to 90% conversion and 100% epoxide selectivity) for olefin epoxidation. The catalyst was successfully recycled up to five cycles without losing much activity and selectivity.

Silica microspheres containing high density surface hydroxyl groups as efficient epoxidation catalysts - Chandra, Prakash; Doke, Dhananjay S.; Shubhangi B. Umbarkar; Vanka, Kumar; Biradar, Ankush V. (RSC Advances, 2015)
Uniformly sized silica microspheres were synthesized by a hydrolysis-condensation method. The obtained material was etched with a mild aqueous potassium hydroxide solution for different periods of time to break their Si-O-Si bonds and increases the density of hydroxyl groups on their surfaces. The resulting materials were then used as transition metal-free catalysts for oxidation of olefins in the presence of hydrogen peroxide as a green oxidant. The materials were thoroughly characterized using various physicochemical techniques. These highly populated hydroxyl groups on the surface of silica microspheres were proven to be responsible for excellent conversion (up to 93%) and epoxide selectivity (up to 100%) for various olefins. Quantum mechanical calculations also corroborate the experimental findings. Furthermore, both experimental and theoretical studies show that tertiary silanols were present at the active sites of the catalyst surface and were responsible for olefin epoxidation.

Tailor made ionic liquids: catalyst and media for organic transformations - Chandra, Prakash; Shinde, Sandip S.; Biradar, Ankush V. (Current Organic Chemistry, 2015)
Ionic liquids are considered as one of the safe, green and environmentally benign solvents/catalysts for many organic reactions. Particularly, imidazolium based ionic liquids attracted much attention in basic as well as applied research. The major role of these ionic liquids is the replacement of the existing corrosive solvents, which are largely used in most of the organic processes and make these processes more eco-friendly. Recent report reveals the importance of imidazolium based ionic liquids, supported on silica gel or polystyrene in catalysis. The solid supports have well versed properties such as easy anchoring of ionic liquid, chemically and mechanically very stable and inert in nature. These ionic liquids can be tailored either by covalent attachment or simple deposition of the ionic liquid on the surface of the support. Both approaches showed enhanced reactivity and selectivity for various reactions. In this review, we made an attempt to review the recent reports related to synthesis and applications of tailor made ionic liquids and their use as catalyst in Aldol, Friedel-Crafts alkylation, hydroformylation, nucleophilic substitution and biomass transformation reactions.
Keywords: Green solvent; heterogeneous catalyst; organic transformation; sustainable process; task-specific ionic liquids

Trifunctional mesoporous silica-based, highly active catalyst for one-pot, three-step cascade reactions - Biradar, Ankush V.; Patil, Vijayshinha S.; Chandra, Prakash; Doke, Dhananjay S.; Asefa, Tewodros (Chemical Communications, 2015)
We report the synthesis of a trifunctional catalyst containing amine, sulphonic acid and Pd nanoparticle catalytic groups anchored on the pore walls of SBA-15. The catalyst efficiently catalyzes one-pot three-step cascade reactions comprising deacetylation, Henry reaction and hydrogenation, giving up to similar to 100% conversion and 92% selectivity to the final product.

Mesoporous tin oxide: an efficient catalyst with versatile applications in acid and oxidation catalysis - Manjunathan, Pandian; Marakatti, Vijaykumar S.; Chandra, Prakash; Kulal, Atul B.; Umbarkar, Shubhangi B.; Ravishankar, Raman; Shanbhag, Ganapati V. (Catalysis Today, 2018)
Mesoporous tin oxide was prepared by template assisted and template-free methods. As-prepared materials were calcined at various temperatures to generate different nature (Bronsted and Lewis), amount and strength of acidic sites. The physico-chemical properties of the catalysts were studied by XRD, N-2 sorption, pyridine-FTIR, NH3-TPD, DRS UV-vis, TGA, SEM, TEM, H-1 MAS and Sn-119 MAS NMR analyses. The catalytic behavior of mesoporous tin oxide catalysts was evaluated for acetalization and ketalization of glycerol with benzaldehyde and acetone respectively under solvent free conditions. The catalytic performance of mesoporous tin oxide was compared with that of other conventional solid acid catalysts namely H-ZSM-5, H-mordenite, H-beta, Al-MCM-41, Al-SBA-15 and Al-TUD-1. The efficiency of mesoporous tin oxide was also tested for cyclohexene epoxidation reaction. The catalyst prepared by template assisted method showed excellent catalytic performance compared to other catalysts due the difference in nature and amount of acidic sites in the catalyst. Meso-SnO2-T-350 was stable and reusable catalyst for four cycles without any appreciable loss in activity, and therefore it offers a good catalyst for potentially wide applications.